Maximum ride : the angel experiment - Patterson, James, 1947- (New York, NY : Warner Vision Books, 2006)
After the mutant Erasers abduct the youngest member of their group, the'birdkids,' who are the result of genetic experimentation, take off in pursuit and find themselves struggling to understand their own origins and purpose
First published in hardcover: Little, Brown, 2005.
Reprint. Originally published
Keywords: Genetic engineering -- Fiction; Adventure stories